Echo's lucky charm - Hapka, Cathy; Hibbert, Hollie (New York : Scholastic, 2015)
Echo is helping her friends, Pearl, Splash, and Flip study for their first test in Magic class at dolphin school, but when Echo loses her lucky shell necklace she is barely able to do any magic until the friends finally find the shell--and a big surprise.
K
600
K
Keywords: Dolphins -- Fiction; Magic -- Fiction; Examinations -- Fiction; Lost and found possessions -- Fiction; Schools -- Fiction